A study of social case work procedure in Johannesburg, with special reference to the standardization of this procedure - Arnold_Louise (African Cinema Unit, 2024)
The growing interest in the qualitative aspects of social work together with modern intereat in methods of social research have resulted in numerous studies in specialized fields l t>f social work. Investigations of those aspects of social research work that are common to all branches of social work are comparatively few in number, although a study of general social work procedure forms the basis of the practical training of every student in social work. Perhaps the most striking conclusion to be drawn from a review of soc hil work li tara. ture as a 'whole is that the authors attempt to set up certain generally acceptable standards in their fields of work and that they do not as a rule succeed in doing so. The failure to set up standards is perhaps partly due to the fact that interest in social research is not always accompanied by a knowledge of scientific procedure; and perhaps the concept 'standard' itself has caused a certain amount of confusion. The term 'standard' may be used to indicate an objective or end 1 or 1 t may be used to indicate a measurement of quality or quantity in which e ,g. the end can be expressed. Family allowances provided at the rate of 5 shillings per child per week may represent a high standard of family allowances to one person, and a low standard to another, dependin~ on individual conceptions of what family allowances should be. But to both these persons the shilling is the standard measurement in which family allowances are expressed. Standards, in the sense of objectives, are dependent on our opinion of what the state of affairs should be.